(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Several approaches and techniques exist to make communication via the internet secure, one of these approaches is steganography. Computer steganography can be defined as a method of hiding data in cover media so that others are not aware of its existence. Quantum computers, built on the principles of quantum physics, have introduced new possibilities for researchers in security and computer science. This paper explores the fundamentals of quantum computing, its achievements, and the challenges and future prospects it presents in the field of cryptography and steganography. Quantum computers give us a new approach to different kinds of complicated problems in security fields by creating multi-state computing spaces. The article deals with the steganography system which hides text inside images and after that realize quantum communication. The secret message is hidden in the cover image using Least Significant Bit (LSB) algorithm. The paper proposes an information transmission scheme with a quantum channel enabled. Quantum key distribution (QKD) is a secure communication method that implements a cryptographic protocol involving components of quantum mechanics.